Impact of Education on Suicides in India - Sharma, Priyank (Journal of Education Culture and Society, 2022)
Aim. The aim of this paper is to examine the impact of education on the rate of suicides in India. The paper further attempts to take a global outlook on how prevalent is suicide among countries with high education indicators. Methodology. The paper is based on secondary research with data collected from National Databases like National Crime Records Bureau and International databases of World Health Organization and Organisation for Economic Co-operation and Development (OECD). Data analysis is done using statistical technique like Correlation and using Microsoft Excel. Results. The study reveals that in India, the increase education levels of people have had negligible impact on the number of suicides in the country. Across states, the suicide rate and literacy rate have a positive correlation of 0.35; while correlation doesn’t mean causation and the two are mildly correlated, it does establish the fact that education doesn’t have a direct impact on the suicide rate. Also, the analysis indicates that even though the education levels in the country have risen, subsequently, the educational level among people who committed suicides also increased. Further, it is found that the countries that are ranked higher on PISA ranking and tertiary education attainment have mostly higher rates of suicide. Conclusions. As shown throughout the study, education hasn’t been an effective instrument in equipping people with life skills: with the increase in education levels across the country, there has been an increase in the education level of people who commit suicides concomitantly, as if the education is happening in vacuum with no effect on the persona of people committing suicides. Thus, it’s significant we question our educational practices; and re-align our goals of education such that it leads to overall development of an individual.